Why wage differences exist across sectors? explanations based on India's industrial sector - Mitra, Arup; Singh, Prakash (2016)
Inter-industry differences in wages are substantial, and over time, they do not seem to be disappearing. Productivity is a determinant of wage differences across industries, though the association between them is not very strong at the aggregate level or for intermediate goods, capital goods, and consumer non-durables. Trade liberalisation enhances productivity and wages at the aggregate level, and also in the case of basic goods and capital goods. However, in an attempt to raise productivity, firms may extract more work from those who are already engaged, and tend to pay them less than their due share in certain industry groups. Contractualisation and feminisation show similar effects for all the industry groups except the intermediate goods industries, and has a worsening effect on wages and also productivity. - Reproduced.
Keywords: India - Industries; Industry; Wages